2012
DOI: 10.1371/journal.pone.0043811
|View full text |Cite
|
Sign up to set email alerts
|

Individual Spatial Responses towards Roads: Implications for Mortality Risk

Abstract: BackgroundUnderstanding the ecological consequences of roads and developing ways to mitigate their negative effects has become an important goal for many conservation biologists. Most mitigation measures are based on road mortality and barrier effects data. However, studying fine-scale individual spatial responses in roaded landscapes may help develop more cohesive road planning strategies for wildlife conservation.Methodology/Principal FindingsWe investigated how individuals respond in their spatial behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 51 publications
2
69
0
2
Order By: Relevance
“…We assume that martens F1, F2 and F3 were residents with well-established territories since they were tracked for long periods, having stable home range areas [15], and F1 and F3 were apparently aware of passage locations for crossings. The movement of these two martens was not hindered by the presence of the highway probably because they knew where to access suitable crossing structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We assume that martens F1, F2 and F3 were residents with well-established territories since they were tracked for long periods, having stable home range areas [15], and F1 and F3 were apparently aware of passage locations for crossings. The movement of these two martens was not hindered by the presence of the highway probably because they knew where to access suitable crossing structures.…”
Section: Discussionmentioning
confidence: 99%
“…However, the choice of mitigation strategy to apply often relies on general patterns, for example road-kill clusters or movement responses [15][17], on the basis that these patterns provide information on the average response of species to roads and traffic. Hence, if individuals vary widely in their responses to roads or mitigation actions and mitigation efforts are directed toward population-level average responses, these efforts may be only partially effective [18][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many of the research studies undertaken on road mortality tended to explore the differences between and within species with the intention of informing more targeted mitigation. For instance, studies considered in this review found that a variety of species-associated factors influenced the rate of wildlife-vehicle collisions, such as age (particularly dispersing juveniles; [19][20][21][22][23]), activity patterns (such as nocturnal and migratory activities; [6,7,24,25]), season (primarily breeding season; [12,[26][27][28][29]), gender (such as males ranging further in the breeding season in search a mate; [23,26,[30][31][32]), diet preferences (e.g., one study found that omnivorous mammals and herbivorous birds were most vulnerable; [33]), mobility (including low-flying species; [15,21,34,35]), behavioral responses (e.g., certain species do not respond to oncoming traffic; [15,36]), and home range size (i.e., the larger the home range the higher the probability of crossing a road; [37]). Another study found that species that were more inconspicuous on the roads were more vulnerable to wildlife-vehicle collisions [38].…”
Section: Direct Impacts Of Roads On Wildlifementioning
confidence: 99%
“…In Europe, USA and Canada some studies tried to understand this (CLEVENGER et al, 2003;GRILO et al, 2009;GRILO et al, 2012;D'AMICO et al, 2015;GARRIGA et al, 2017) and concluded that temperature influences roadkill (D'AMICO et al, 2015;GARRIGA et al, 2017). In Brazil, we have just started, our researches investigate if there are more roadkill in the rainy or dry season (BUENO; ALMEIDA, 2010;RAMOS et al, 2011;BRAZ;FRANÇA, 2016) or the stretches of the highway with higher roadkill rates (CÁCERES et al, 2012;BUENO et al, 2012;SANTANA, 2012;FERREIRA et al, 2014;CARVALHO et al, 2015;ASCENSÃO et al, 2017;SANTOS et al, 2017).…”
Section: Introductionmentioning
confidence: 99%